Comparing dividend puzzle solutions by Polish, Canadian, Norwegian and American executives - Agata Sierpińska-Sawicz (Contemporary Economics, 2016)
This study compares firms' dividend policy antecedents in four countries. The author surveys managers of 230 companies listed on the Warsaw Stock Exchange that paid dividends over the 2001-12 period and compares the findings to survey reports from the USA, Canada, and Norway. The main antecedents of dividend policy in these countries are the level of current earnings, their stability over time, the level of expected earnings and the pattern of past dividends. The last factor is of little importance for Polish managers, as the history of dividend payouts in Polish-listed companies is brief. The establishment of factors that shape the dividend policy in public companies has crucial importance in global financial markets. Investors make cash transfers to markets that ensure a high return on invested capital. Orders from foreign investors generate almost 50% of the turnover on the Warsaw Stock Exchange. Therefore, in their decisions on the division of earnings, Polish companies should be guided by similar considerations as those displayed by companies in developed economies that seek to attract foreign investors. The study expands on the existing survey research on dividends and provides new evidence from managers of companies in Poland.
Keywords: G35; 330; dividend; survey; dividend policy; dividend antecedents; dividend determinants